ANALISIS PENERAPAN POLA FREEMIUM DALAM MODEL BISNIS APLIKASI STREAMING MUSIK (Studi Pada Aplikasi Streaming Musik LangitMusik) - Ziemans Hendratama Majid; M. Kholid Mawardi (Jurnal Administrasi Bisnis, 2018)
This research is a descriptive research with qualitative approach. The results of research related to aspects in Business Model Canvas obtained that the value proposition formed by LangitMusik is free quota streaming, instant access to million songs, and huge platform for advertising. Customer segments targeted are telkomsel users, music listener, and advertiser. Channels used in delivering value proposition to the consumer are mobile app and web player. Customer relationship that is applied is playlist update, social media engagement, music event, sponsorship, and FGD. Revenue streams are obtained from bundling with Telkomsel products, subscription fees, and advertising revenue. Key resources are digital platform, human resource, and songs collection. Key activities include research, platform development and marketing activities. Partners who became key partnership LangitMusik is record label, telkomsel, melon Indonesia, and artist / musician. Cost structure that must be spent is web & app development, marketing & sales, administration, and the product development. Keywords: Freemium, business model canvas АBSTRАK Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian terkait dengan aspek-aspek dalam Business Model Canvas diperoleh bahwa value proposition yang dibentuk oleh LangitMusik adalah  free quota streaming, instant access to million  songs, dan huge platform  for advertising. Customer segments yang ditargetkan yaitu   telkomsel users, music listener, dan advertiser. Channel yang digunakan dalam menyampaikan value proposition ke konsumen adalah mobile app dan web player. Customer relationship yang diterapkan adalah playlist update, social media engagement, music event, sponsorship, dan FGD. Revenue streams didapatkan dari bundling dengan produk telkomsel, subscription fee, dan advertising revenue. Key resources berupa digital platform, human resource, dan songs collection.  Key activities berupa research, platform development dan kegiatan marketing. Mitra yang menjadi key partnership LangitMusik adalah record label, telkomsel, melon Indonesia, dan artis/musisi. Cost structure yang harus dikeluarkan adalah web & app development, marketing & sales, administration, dan product development. Kаtа Kunci: Freemium, business model canvas